Regional Study on Targeting Systems and Practices : Draft Policy Note - Sanchez-Paramo, Carolina (World Bank, Washington, DC, 2013)
This policy note aims to take stock of regional experiences in the area of targeting, both in the context of government systems and the World Bank's operational work, in South Asia. The main objectives are to review targeting systems and practices in the context of government programs; to critically review the role for and impact of targeting in the WB's operational work; and to extract lessons that can be used to deepen the relevance and impact of the WB's operational work in South Asia. The evidence presented in this note will serve as a resource for those interested in and/or planning some work on targeting related work in the region. In this sense, by presenting information on both country systems and performance of WB-led work, the note targets both practitioners and managers. The analysis focuses first on the architecture of targeting systems in South Asia, and on the determinants of targeting effectiveness, including the choice and design of the targeting tool, implementation and monitoring of the targeting tool, and the design, implementation and monitoring of the targeted program. The note concludes that international evidence a large fraction of the observed differences in targeting effectiveness across systems and programs, can be attributed to factors related to implementation and monitoring. This implies that investments aimed at correcting resource, capacity and logistic limitations in government systems could go a long way in improving targeting outcomes in the region.